Yesterday, I posted this problem in Romanian Mathematical Magazine: Editor Prof. Dan Sitaru.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
The given integral is π 1 ∫ 0 1 a 3 ( 1 − a 2 ) 3 d a , where a = e − π m . The value of the integral is 4 0 π 1 . Therefore β = 4 0
Problem Loading...
Note Loading...
Set Loading...
Original post where i shared my solution.
For convenience we write a = e − π m and our matrix H ( m ) reduces to H ( m ) = ⎝ ⎜ ⎜ ⎛ a a 2 a 3 a 4 a 2 a a 2 a 3 a 3 a 2 a a 2 a 4 a 3 a 2 a ⎠ ⎟ ⎟ ⎞ We note that H ( m ) is a 4 × 4 Square Matrix .So to determine the det ( H ( m ) ) we can exploit the general formula for n × n Square matrix as Δ = i = 1 ∑ n j = 1 ∑ n ( − 1 ) i + j a i j M i j = i , j ∑ n ( − 1 ) i + j a i j M i j Now for 1 ≤ k ≤ 4 a k = e − k π m = 0 which implies H ( m ) doesn't have any 0 entries and taking any row and columns the determinant doesn't change justified by Laplace expansion . We take j = 1 and then Δ = i , 1 ∑ 4 ( − 1 ) i + 1 a i 1 M i 1 = a 1 1 M 1 1 − a 2 1 M 2 1 + a 3 1 M 3 1 − a 4 1 M 4 1 ⋯ ( 1 ) here M i j is the corresponding minors so we calculate the minors as M 1 1 = ∣ ∣ ∣ ∣ ∣ ∣ a a 2 a 3 a 2 a a 2 a 3 a 2 a ∣ ∣ ∣ ∣ ∣ ∣ = a ∣ ∣ ∣ ∣ a a 2 a 2 a ∣ ∣ ∣ ∣ − a 2 ∣ ∣ ∣ ∣ a 2 a 3 a 2 a ∣ ∣ ∣ ∣ + a 3 ∣ ∣ ∣ ∣ a 2 a 3 a a 2 ∣ ∣ ∣ ∣ = a 3 − 2 a 5 + a 7 here calculating the minors like that of M 1 1 we can obtained that M 2 1 = a 4 − 2 a 6 + a 8 and M 3 1 = M 4 1 = 0 . Plugging the obtained values in 1 we have Δ = a 1 1 M 1 1 − a 2 1 M 2 1 = a ( a 3 − 2 a 5 + a 7 ) − a 2 ( a 4 − 2 a 6 + a 8 ) and hence det ( H ( m ) ) = a 4 ( 1 − 3 a 2 + 3 a 4 − a 6 ) . since H ( m ) is an invertible Matrix ⇒ H ( m ) ⋅ H ( m ) − 1 = I 4 ⇒ det ( H ( m ) ) ⋅ H ( m ) − 1 = 1 ⇒ det ( H ( m ) = det ( H ( m ) − 1 ) 1 = a 4 ( 1 − 3 a 2 + 3 a 4 − a 6 ) where I 4 is identity matrix hence
∫ 0 ∞ e − 4 π m ( 1 − 3 e − 2 π m + 3 e − 4 π m − e − 6 π m ) d m = 4 π 1 − 6 π 3 + 8 π 3 − 1 0 π 1 = 4 0 π 1 Therefore required β = 4 0 .